Effects of injection marination with various calcium sources and molar concentrations on display color life, tenderness, and microbial inhibition of beef loin steaks - T.E. Lawrence; Melvin C. Hunt; Michael E. Dikeman; Curtis L. Kastner; James L. Marsden (Kansas Agricultural Experiment Station Research Reports, 2002)
Beef strip loins were assigned to one of 11 treatments that included injection marination (10% by weight) with three calcium salts at three molar concentrations, a distilled water control, and a non-marinated control. The effects of calcium salt and concentration were tested for retail display color life, tenderness and sensory traits, and microbial growth. Calcium lactate marinated steaks had longer color life and less microbial growth than those treated with calcium chloride or calcium ascorbate. Increasing molar concentration (.1M to .2M to .3M) caused faster color deterioration, and did not significantly improve microbial inhibition. All calcium treatments improved tenderness; however, calcium chloride treatments induced off-flavors. Considering a whole system approach that accounts for color life, microbial inhibition, shear force, and sensory traits, we recommend injecting beef longissimus with 10% of a .1M solution of calcium lactate, and do not recommend other calcium salts or concentrations.
Keywords: Cattlemen& #x27; s Day; 2002; Kansas Agricultural Experiment Station contribution; no. 02-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 890; Beef; Marination; Calcium; Color life; Tenderness; Microbial inhibition; Loin steaks